Stochastic mortality, subjective survival expectations, and individual saving behavior - Thomas Post; Katja Hanewald (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Theoretical studies suggest that unexpected changes in future mortality and survival probabilities (stochastic mortality) are important determinants of individuals' decisions about consumption, saving, asset allocation, and retirement timing. Using data on subjective survival expectations elicited in the Survey of Health, Ageing and Retirement in Europe (SHARE) and corresponding life table data from the Human Mortality Database (HMD), we find evidence of respondents' awareness of stochastic mortality. We also find that respondents' saving behavior is influenced by stochastic mortality perceptions.
Keywords: D14; D84; D91; H31; J11; 330; stochastic mortality; subjective survival expectations; forecast dispersion; savings behavior; Sterblichkeit; Stochastischer Prozess; Erwartungstheorie; Sparen; Alte Menschen; Europa